2017
DOI: 10.1097/igc.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Circulating Tumor Cells in Ovarian Cancer: A Meta Analysis

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…In the PB group, it showed that patients with positive CTCs had significantly shorter overall survival (OS) and disease-free survival (DFS) than patients with negative CTCs (HR, 2.09; CI, 1.13-3.88 and HR, 1.72; CI, 1.32-2.25, respectively). The same result was shown with DTCs in the BM group (HR, 1.61; CI, 1.27-2.04 and HR, 1.44; CI, 1.15-1.80, respectively) [305].…”
Section: Other Cancerssupporting
confidence: 79%
“…In the PB group, it showed that patients with positive CTCs had significantly shorter overall survival (OS) and disease-free survival (DFS) than patients with negative CTCs (HR, 2.09; CI, 1.13-3.88 and HR, 1.72; CI, 1.32-2.25, respectively). The same result was shown with DTCs in the BM group (HR, 1.61; CI, 1.27-2.04 and HR, 1.44; CI, 1.15-1.80, respectively) [305].…”
Section: Other Cancerssupporting
confidence: 79%
“…8,9 Three aspects of selection, comparability, and exposure (9 scores in total) were carefully judged. Studies of moderate or high quality were included (score of 5 or higher).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“… 5 Although some smaller studies found no correlation of CTCs with disease progression, four recent meta-analyses showed that CTC positivity in ovarian cancer patients was significantly associated with shorter overall, disease-free, and progression-free survival as well as advanced stage in ovarian cancer. 6 9 …”
Section: Introductionmentioning
confidence: 99%